2018
DOI: 10.1186/s13098-018-0321-x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of lixisenatide as an add on therapy to basal insulin in diabetic type 2 patients previously treated with different insulin regimes: a multi-center observational study

Abstract: IntroductionThis observational study aimed to assess the effectiveness of lixisenatide as add on therapy to basal insulin in diabetic type 2 patients previously treated with different insulin regimes.MethodsPatients with diabetes type 2, prescribed with lixisenatide and basal insulin were divided in three groups (premixed insulin, basal bolus insulin and basal oral therapy (BOT). Difference in mean change in HbA1c, body mass index, total insulin doses, fasting blood glucose (FPG) and prandial blood glucose (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…Many treatment algorithms and clinical trials of T2DM with beta cell death have been proposed so far [31][32][33][34] . Basal-Bolus, Basal plus, Basal supporting oral therapy (BOT), premixed insulins and premixed insulin and GLP-1R agonist were reported to improve safety and efficacy of the patient treated mainly in out-patient clinic [35][36][37][38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…Many treatment algorithms and clinical trials of T2DM with beta cell death have been proposed so far [31][32][33][34] . Basal-Bolus, Basal plus, Basal supporting oral therapy (BOT), premixed insulins and premixed insulin and GLP-1R agonist were reported to improve safety and efficacy of the patient treated mainly in out-patient clinic [35][36][37][38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…The search terms are presented in Table S1. The search results were discussed by the author group and relevant articles were identified; 19–33 these are summarised in Tables 1 and 2 19–33 …”
Section: Methodsmentioning
confidence: 99%
“…During the 3–6‐month follow‐up period, transitioning from BBI to basal insulin and lixisenatide significantly reduced HbA1c (−22 mmol/mol [−2%]; p < 0.001), body weight (from 107 to 98 kg; p < 0.001) and TDD (−21.0 U; p = 0.006) (Table 2). 25 Hypoglycaemia data were not collected in this study.…”
Section: Overview Of the Clinical Evidence For Transitioning To A Com...mentioning
confidence: 98%
See 1 more Smart Citation
“…Lixisenatide, a once daily 7 , 9 short‐acting GLP‐1RA, improves glycemic control by increasing postprandial insulin secretion, delaying gastric emptying and reducing postprandial glucagon 10 . Various studies have reported that adding lixisenatide to basal insulin (BI) with or without other oral antidiabetic drugs led to significant reduction in glycated hemoglobin (HbA1c) levels in type 2 diabetes mellitus patients 9 , 11 , 12 , 13 , 14 . The results from these studies also showed that adding lixisenatide to BI led to weight reduction, as opposed to the usual weight gain, with lower risk of hypoglycemia and lower total insulin dose.…”
Section: Introductionmentioning
confidence: 99%